Pengaruh Penambahan Limbah Plastik Low Density Polyethylene Terhadap Karakteristik Campuran Laston AC-WC - Erni, Dwi Susanti; Rifqi, Mirza Ghulam; Amin, M. Shofi'ul (Journal of Applied Civil Engineering and Infrastructure Technology, 2021)
The problem of plastic waste is now one of the world's concentrations. Efforts to reduce and prevent many have been done, but in general the results obtained are not comparable with the growing use of plastics that continues to increase, especially plastics that are not managed properly. One of the efforts made is the utilization of plastic waste as added ingredients of Laston AC-WC hot asphalt mixture called modification. The purpose of this study was to determine how the effect of adding Low Density Polyethylene (LDPE) plastic waste to the characteristics of Marshall Laston AC-WC. Tests carried out include aggregate testing, asphalt testing, and plastic testing, and Marshall testing. The design of the mixture is done by dry (dry process) using a variation of plastic content of 0%, 4.5%, 5%, and 5.5%, each of which uses 5 levels of asphalt which is 5%, 5.5%, 6% , 6.5%, and 7% with 3 specimens each, so that there are a total of 75 specimens. Marshall test results obtained KAO of 6.5% with a variation of plastic content of 5.5%, obtained stability of 2167.40 kg, Flow 3.8 mm, VIM 3.94%, VMA 15.95%, VFA / VFB 77, 12%, and MQ 570.37 kg / mm. So that the addition of LDPE type plastic waste meets (General Specifications of Bina Marga, 2018).